Epicatechin Mitigates Anxiety-Related Behavior in a Mouse Model of Obesity by Modulating Gut Microbiome Composition and Global Gene Expression Profile in the Hippocampus. (14th June 2022) - Milenkovic, Dragan; Kang, Jiye; Wang, Ziwei; Cremonini, Eleonora; Vauzour, David; Oteiza, Patricia
Abstract: Objectives: Epicatechin (EC) is a flavan-3-ol abundant in cocoa, apples, and tea, and can prevent vascular dysfunction and development of diseases, such as cardiovascular or neurodegenerative diseases. We have recently shown that EC can prevent lipid-induced brain endothelial cell dysfunction by modulating the expression of protein-coding and non-coding genes (miRNAs, long non-coding RNAs). The aim of our study is to investigate the capacity of EC to mitigate the adverse effects of high-fat diet (HFD) on cognitive function, the gut microbiota dysbiosis, metabolic and inflammatory markers as well as to decipher the molecular mechanisms of EC action. Methods: Healthy eight-weeks old male mice were fed for 24 weeks either: A) a control diet containing 10% total calories from fat; B) a HFD containing 45% total calories from fat; or c) a HFD supplemented with EC (20 mg/kg BW). Plasma metabolic parameters, cognitive tests (open field test, novel object recognition test, Morris water maze), gut microbiota profile (16S sequencing), and genomic modifications (Affymetrix arrays) in the hippocampus followed by in-depth bioinformatic analyses were performed. Results: EC supplementation resulted in amelioration of HFD-induced increase in plasma glucose and insulin, mitigated anxiety-related behaviors and modulated affected the microbiota composition by affecting abundance of 139 taxa. Transcriptomic analysis demonstrated that EC induced significant changes in the hippocampal gene expression of mice fed with the HFD. We observed changes in expression of 1001 genes corresponding to protein-coding genes, 241 miRNAs, and 167 long non-coding RNAs. The PCA and heatmap analysis revealed opposite expression of genes obtained following EC supplementation when compared to the gene expression profile obtained after consumption of the HFD. Functionality analysis revealed that the differentially expressed gene regulate processes involved in neurofunction, inflammation, cell-cell adhesion, and cell signaling. Conclusions: In summary, EC supplementation mitigated anxiety-related behavior in a model of diet-induced obesity in mice, which can be in part mediated through the modulation of gut microbiota and by reversing HFD-induced complex genomic modification in the hippocampus. Funding Sources: NIH grants R01DK090492 and R01DK095359. France-Barkley foundation.